RELEVANSI PEMIKIRAN MAHMUD YUNUS DALAM KITAB AT-TARBIYAH WA AT-TA’LIM DENGAN KOMPETENSI GURU (UNDANG-UNDANG NOMOR 14 TAHUN 2005) - Umi Salamah; Abdulloh Safiq (STAI Ma'had Aly Al-Hikam Malang, 2019)
Education is experiencing challenges in the 21st century, all kinds of aspects of human needs are progressing very rapidly, both in science, technology, information, even social patterns of humanity / society. Teachers as professionals aim to implement the national education system and realize national education goals, namely the development of the potential of students to become human beings who believe and fear God Almighty, noble, healthy, knowledgeable, competent, creative, independent, and become citizens democratic and responsible country. Teachers must have competence in carrying out their duties as an educator and as part of the community. The purpose of this study was to determine the views of Mahmud Yunus about the competence of teachers in the book at-Tarbiyah wa at-Ta'lim, and the relationship between the views of Mahmud Yunus in the book at-Tarbiyah wa at-Ta'lim with teacher competence according to Law no. 14 of 2005. This type of research is library research, using a philosophical-historical approach. The philosophical approach is used to discuss the concept of Mahmud Yunus's thought, while historically it aims to study and explain the biography, work and life side of the teacher's competence according to Law No. 14 of 2005 there were four, covering pedagogical competencies, personality competencies, social competencies, and professional competencies. Teacher competence according to Mahmud Yunus can be seen in four aspects, including: pedagogical aspects, personality aspects, professional aspects, social aspects. When linked and adjusted to the current conditions and needs of teacher competence, it turns out to be very appropriate and interrelated, because the thought offered there is a bond of mutual support with current theories of teacher competence, and is very suitable to be a reference in the development of learning processes even relevant to education Islam